d13C values measured by Secondary Ion Mass Spectrometry in shells of the planktic foraminifer Morozovella allisonensis from the PETM section of ODP Site 865 (Central Pacific) - Reinhard Kozdon; Daniel Clay Kelly (PANGAEA, 2024)
Foraminiferal shells of the species M. allisonensis from the PETM section of ODP Site 865, Central Pacific, were cast with 3 grains of UWC-3 calcite standard (Kozdon et al., 2009) in the center of a 25 mm round epoxy mount, ground to the level of best exposure, polished, cleaned, and Au-coated. Prior to geochemical analysis, shells were examined by Scanning Electron Microscopy (SEM) to identify subdomains suitable for in-situ d13C and Mg/Ca ratio measurements and to avoid diagenetically altered zones within each shell. In-situ d13C measurements were performed with ~7 μm beam spot size in the WiscSIMS Laboratory at UW-Madison by a CAMECA ims-1280 large radius multicollector ion microprobe) using the protocols described in a previous study (Kozdon et al., 2018). The in-situ d13C microanalyses primarily targeted subdomains located at the base of pustular outgrowths (muricae) along the chamber walls of each shell. Previous studies have shown that these subdomains are less susceptible to post-depositional alteration than the rest of the shell (Kozdon et al., 2011; Kozdon et al., 2013). Between one and five SIMS d13C microanalyses were performed for each shell. Reproducibility of the individual spot analysis of UWC-3 standard (d13C = -0.91 extperthousand V-PDB, Kozdon et al., 2011) bracketing samples is on average 0.7 extperthousand (± 2 SD).